AERODROME CONTROL TOWER NOISE LEVEL at AJI PANGERAN TUMENGGUNG PRANOTO - Sa'adi, Rayhan Almer Sa'adi; Sonhaji, Imam (Politeknik Penerbangan Surabaya, 2024)
This study was conducted at Aji Pangeran Tumenggung Pranoto International Airport in Samarinda to measure the impact of noise levels in the airport's cabin control tower on flight safety. In this study, descriptive and qualitative methods were used. Data collection was conducted through a documentary study and direct on-site observation from February to March 2021. The results showed that the noise level in the cabin control tower at Aji Pangeran Tumenggung Pranoto Samarinda International Airport can affect the air traffic controller's concentration. It is required to handle the cabin aerodrome control tower to increase the security of flight movements. In addition, the installation of headsets and silencers is required in accordance with the applicable regulations on the equipment and scope of the air traffic controller's workspace.